Induction of Barley Silicon Transporter HvLsi1 and HvLsi2, increased silicon concentration in the shoot and regulated Starch and ABA Homeostasis under Osmotic stress and Concomitant Potassium Deficiency - Hosseini, Seyed A.; Maillard, Anne; Hajirezaei, Mohammad R.; Ali, Nusrat; Schwarzenberg, Adrian; Jamois, Frank; Yvin, Jean-Claude (Frontiers in Plant Science, 2017)
Drought is one of the major stress factors reducing cereal production worldwide. There is ample evidence that the mineral nutrient status of plants plays a critical role in increasing plant tolerance to different biotic and abiotic stresses. In this regard, the important role of various nutrients e.g. potassium (K) or silicon (Si) in the mitigation of different stress factors, such as drought, heat or frost has been well documented. Si application has been reported to ameliorate plant nutrient deficiency. Here, we used K and Si either solely or in combination to investigate whether an additive positive effect on barley growth can be achieved under osmotic stress and which mechanisms contribute to a better tolerance to osmotic stress. To achieve this goal, barley plants were subjected to polyethylene glycol (PEG)-induced osmotic stress under low or high K supply and two Si regimes. The results showed that barley silicon transporters HvLsi1 and HvLsi2 regulate the accumulation of Si in the shoot only when plant suffered from K deficiency. Si, in turn, increased the starch level under both osmotic stress and K deficiency and modulated the glycolytic and TCA pathways. Hormone profiling revealed that the beneficial effect of Si is most likely mediated also by ABA homeostasis and active cytokinin isopentenyl adenine (iP). We conclude that Si may effectively improve stress tolerance under K deficient condition in particular when additional stress like osmotic stress interferes.